Analysis of the current situation and influencing factors of information technology education in middle school - Jia, Xiaoqiang; He, Xiaohu; Wang, Jing (Applied mathematics and nonlinear sciences, 2022)
The development of science and technology is becoming more and more rapid, and the educational empowerment of information technology (IT) in middle schools is becoming more and more obvious. The interesting and operational aspects of IT are suitable for middle school students, who are gradually becoming more rational in their thinking and problem-solving skills, and who are curious to discovering new things. This paper analyses the factors influencing the acceptance of IT education among middle school students by reviewing a large amount of literature and compiling technology-related theories. The research variables are determined by combining the characteristics of middle school students, and a structural equation model is constructed to select the factors influencing the acceptance of technology in secondary school IT classrooms, and the hypothesis is proposed, tested and revised, and then the scientific and effective measures are proposed according to the model. By the statistical analysis of variables, it can be seen that the average values of perceived ease of use and social influence (SI) are relatively high, which are 3.9899 and 4.1933, respectively, indicating that SI and subjective initiative have significant positive correlations with the behavioural intentions of middle school students in learning IT. As technological literacy is low, with an average value of only 3.4966, the influence of the technological literacy of IT on middle school students’ learning ability is not significant. This reflects the degree of middle school students’ mastery of the knowledge of IT, which is not enough. Further, the initiative of learning in the network is low and the needs of teachers in IT classes indirectly affect students’ learning initiative. It is hoped middle school students learn IT through the network by their initiative and provide guidance for teachers in teaching, to promote the application and deep popularity of IT in secondary school education.